KETERWAKILAN PEREMPUAN SEBAGAI ANGGOTA LEGISLATIF DI DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI - Maharani, Rizki; Ramadhani, Rizki (Bahasa Indonesia, 2022)
This study discusses the role of women in the legislature, especially in the Regional House of Representatives of Province. Women in Indonesia are formally strong enough because there are many provisions in various laws and other regulations that provide juridical protection for women. The representation of women in the dissertation legislature is actively involved in the legislative decision-making process, budgeting and supervision will produce gender-responsive government and development policies as strategic instruments to realize gender justice and equality in various aspects of development. However, the role of women as members of the legislature is still undervalued, including members of the legislature in the Regional House of Representatives of Province. In this case, analyze the problem by using an institutional approach. The institutional approach is one that explains what should be, not what it really is. The main idea of ​​institutional theory is that organizations are shaped by the institutional environment that surrounds them. There are four concepts from the institutionalism approach, namely Categorical Adjustments, Structural Adjustments, Procedural Adjustments and Personnel Adjustments.